Structural modifications in silica sonogels prepared with additions of poly(vinyl alcohol) - Portella, J. A. [UNESP]; Donatti, D. A. [UNESP]; Ruiz, Alberto Ibanez [UNESP]; Vollet, D. R. [UNESP] (Amer Chemical Soc, 2008)
Silica wet gels were prepared from acid sonohydrolysis of tetraethoxysilane (TEOS) and additions of poly(vinyl alcohol) (PVA)-water solution. Aerogels were obtained from supercritical CO(2) extraction. The samples were studied by thermal gravimetric (TG) analysis, small-angle X-ray scattering (SAXS), and nitrogen adsorption. The structure of wet gels can be described as a mass fractal with dimension D equal to 2.0 on the whole length scale experimentally probed by SAXS, from similar to 0.3 to similar to 15 nm. Pure and low-PVA-addition wet gels exhibit an upper cutoff accounting for a finite characteristic length xi of the mass fractal structure. Additions , of PVA increase without modifying D, which was attributed to a steric effect of the polymer in the structure. The pore volume fraction of the aerogels diminishes typically about 11% with respect to that of the wet gels, although nitrogen adsorption could be underestimating some porosity. The pore size distribution of the aerogels is shifted toward the mesopore region with the additions of PVA, in a straight relationship with the increase of xi in the wet gels. The thermal stability of the pore size distribution of the aerogels was studied up to 1000 degrees C.